2003
DOI: 10.1209/epl/i2003-00256-8
|View full text |Cite
|
Sign up to set email alerts
|

MgB 2 two-gap superconductivity with intra- and interband couplings

Abstract: A two-band model of MgB2 superconductivity is developed. It exploits repulsive σ-π interband coupling besides the σ-intraband electron-phonon attraction and Coulomb interaction. With an adjustable set of parameters the observed dependences of the gaps, specific heat and second critical magnetic field on temperature, furthermore Tc vs. Al-doping, and the Tc isotope effect exponent are reproduced without further fittings. The unconventional MgB2 superconductivity can be ascribed to the specific band structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
(35 reference statements)
2
19
0
Order By: Relevance
“…For MgB 2 , with an unexpectedly high transition temperature (T c ) [2] among the phonon-mediated superconductors [3], however, evidence for a multiple gap, exhibiting marked deviation from expectations for a simple isotropic gap, has been obtained from k-integrated probes [4]. Therefore, the origin of the multiple gap and its relation to the mechanism yielding such a high T c are strongly debated [5][6][7][8][9]. The most plausible candidate so far widely accepted is the two-band superconductivity model, which predicts a large difference in SC-gap size on different bands [or Fermi surface (FS) sheets] [10].…”
mentioning
confidence: 99%
“…For MgB 2 , with an unexpectedly high transition temperature (T c ) [2] among the phonon-mediated superconductors [3], however, evidence for a multiple gap, exhibiting marked deviation from expectations for a simple isotropic gap, has been obtained from k-integrated probes [4]. Therefore, the origin of the multiple gap and its relation to the mechanism yielding such a high T c are strongly debated [5][6][7][8][9]. The most plausible candidate so far widely accepted is the two-band superconductivity model, which predicts a large difference in SC-gap size on different bands [or Fermi surface (FS) sheets] [10].…”
mentioning
confidence: 99%
“…The concept of the two-band superconductivity and the possibility of the superconductivity have been introduced by many groups [11][12][13][14]. In summary of the concept, when the Fermi energy level crosses two bands, we can consider two Cooper pairs around their Fermi wavenumber.…”
mentioning
confidence: 99%
“…It has been fitted with an asymmetric Lorentzian with Fano line-shape [8] centred at z=0, with the half width /2=300 meV and an asymmetry parameter q=4. This experimental curve provides the clear experimental evidence for the T c enhancement driven by interband pairing shows a resonance centred at z=0, as expected for Feshbach shape resonanceIn conclusion we have discussed the Feshbach shape resonances around a type (I), type (II) and type (III) ETT in heterostructures and in the particular case of MgB 2 where the two band scenario is well established [205][206][207], we have shown that the Feshbach shape resonance in interband pairing occurs in a superlattice of superconducting layers near a type (II) ETT in this particular multiband superconductor in the clean limit. The Feshbach shape resonance increases the critical temperature from low T c diborides up to T c =40K in MgB 2 and it provides the most clear case of T c amplification beyond the limit of 20K.…”
supporting
confidence: 66%